Reading comprehension and academic writing in engineering students from the Faculty of Industrial and Systems Engineering at a public university - Abanto Atauje, Roxana (2019)
The purpose of this research is to know the relationship between reading comprehension and text writing at a university in metropolitan Lima. The research approach is quantitative based on the descriptive-correlational design. The sample consisted of 59 students from the Faculty of Industrial and Systems Engineering, at a university of metropolitan Lima, located in the city of Lima, Peru. The sample was obtained thanks to a statistical calculation; however, it was increased to 71 students during the application of the reading comprehension and academic writing tests, in order to make it more representative. For data collection techniques, observation, documentary analysis and statistical analysis were applied. It is concluded that there is a direct and significant relationship between literal and inferential levels and academic writing, while critical level does not comply with that relationship.